The Struggle for Integration of Refugees and Immigrants: Examples of Integration of Refugees in European Cities and the Case Study of Athens (European Journal of Formal Sciences and Engineering, 2022)
This paper focuses on the integration of refugees and immigrants into Greek society through the provision of housing. This topic is a hot one due to the fact that many refuges have arrived in Greece during the previous years and there is a need to remain for a long time. Thus, the provision of housing is imperative. However, due to the economic crisis, the creation of such spaces is expensive and unachievable. As a result, alternatives should be examined. For this purpose, different policies of the smooth integration of refugees and immigrants in European countries can provide such solutions. Three case studies were selected across Europe and they have been compared to the Athenian paradigm. Through this research, proposals about their successful integration have been derived. In that way, it will be possible to provide specific plans that reorganize various areas in Athens in order to make this vision a reality.
Keywords: refugees, immigrants, integration, non-used buildings, case studies, Athens.